Exploring special economic zone governance: a comparative study of Kazakhstan, the Russian Federation, and Kyrgyzstan - N. Saulius; A. Konysbek (Хабаршысы. Экономика сериясы)
The world experience shows many successful cases of the development of special economic zones. Effective governmental regulations on this matter are crucial for creating a favorable infrastructure and reducing administrative barriers for investors. Accordingly, this article explores and analyzes the public administration tools in terms of governance of special economic zones of Kazakhstan, Russia and Kyrgyzstan. The aim of the research is provision of secondary data analysis of the effectiveness of governance in three countries.